2004
DOI: 10.1074/jbc.m400456200
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Access to the Rat Major Histocompatibility Complex Class I Peptide-loading Complex Reveals Optimization of Peptide Cargo in the Absence of Transporter Associated with Antigen Processing (TAP) Association

Abstract: Major histocompatibility complex (MHC) class I molecules load peptides in the endoplasmic reticulum in a process during which the peptide cargo is normally optimized in favor of stable MHC-peptide interactions. A dynamic multimolecular assembly termed the peptideloading complex (PLC) participates in this process and is composed of MHC class I molecules, calreticulin, ERp57, and tapasin bound to the transporter associated with antigen processing (TAP) peptide transporter. We have exploited the observation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…This is in agreement with previous studies demonstrating an increased calnexin binding of mouse L d N86K, L d N86Q, and L d S88W mutants (15,16), but not with studies on human A2S88A and etB27N86Q mutants in which calnexin binding was found to be weak and conserved (35) or had not been tested (22). Similar to L d mutants and etB27N86Q (15,16,22,23), Cw1S88G lost its ability to bind calreticulin, ERp57, and tapasin in peptide loading-sufficient cells, but unlike the above mutants (and remarkably) it did retain partial interaction with TAP.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is in agreement with previous studies demonstrating an increased calnexin binding of mouse L d N86K, L d N86Q, and L d S88W mutants (15,16), but not with studies on human A2S88A and etB27N86Q mutants in which calnexin binding was found to be weak and conserved (35) or had not been tested (22). Similar to L d mutants and etB27N86Q (15,16,22,23), Cw1S88G lost its ability to bind calreticulin, ERp57, and tapasin in peptide loading-sufficient cells, but unlike the above mutants (and remarkably) it did retain partial interaction with TAP.…”
Section: Discussionsupporting
confidence: 81%
“…However, the glycosylation-defective mutants RT-1A a N86K and etB27N86Q (22,23) were assembled in vitro following bulk isolation from non-ionic detergent cell extracts whereas Cw1S88G was isolated at different, carefully selected chase points, providing the opportunity to observe an initial refractoriness to binding peptides (similar to etB27N86Q) followed by the stabilization of abnormal class I folds (possibly reminiscent of RT-1A a N86K). The present observations may in part reconcile the available, conflicting evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The propensity of newly synthesized B*27:05 to misfold and aggregate has long been suggested to correlate with AS etiology [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…4B, middle and bottom panels). The relation between full-length US3 and the truncated isoform was further investigated in 293T cells that express little tapasin (13). The 293T cells were cotransfected with cDNAs as indicated and analyzed by coprecipitation and immunoblot (Fig.…”
Section: Resultsmentioning
confidence: 99%